Revisiting Mothers’ Identity in Sharenting in Digital Era: Indonesian Mothers’ Neoliberal Performativity and Media Engagement - Triastuti, Endah; Siahaan, Rony Agustino (CARAKA : Indonesia Journal of Communication, 2024)
This study revisits the notion of sharenting by providing a study within Indonesia context. Scholarship discusses sharenting and concludes that as a practice, sharenting does not resemble what constitutes the identity of a 'good mother' and risk children’s safety online. This study reframes Employing argument on identity and performativity, this study demostrates the neoliberal mothers have established a new image of ‘a good mother’, especially within their engagement with digital media. Employing the digital ethnography approach, this study collect data from both online observations as well as depth interviews with mothers who are engaged with sharenting practices. Focusing on sharenting practices on 8 Indonesian mothers, this study agrees that identity of a good mother is not fixed, yet it is very conflictual and progressive. Mothers do not only show agency in claiming the performativity, yet they are also aware the consequence of the claim. Following the neoliberal narrative of the intensive motherhood, this study shows that mothers renarrate identity of a good mother as discipline, happy, grateful, competitive, resilient, hardworking and adept at risk management including managing children safety risk online. At the same time, mothers remain preserving the dominant identity of a good mother, who fully devote themselves to the childrearing activities. This study conclude that mothers’ agency in claiming new forms of identity in the neoliberal regime portrays the notion of the subject-in-process, that mothers’ performativity in neoliberal regime is both subversive, yet preserving the dominant identity of mother, and beyond.